EFEKTIVITAS PROGRAM CORPORATE SOCIAL RESPONSIBILITY (CSR) PT.PERKEBUNAN NUSANTARA V WILAYAH KEBUN SEI INTAN KABUPATEN ROKAN HULU - Riki Riyandri; Dadang Mashur (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
This research is based on the phenomenon of ineffectiveness of CSR program implemented by PT. Perkebunan Nusantara V area of Sei Intan Garden of Rokan Hulu Regency is Kemitraaan program has not been implemented effectively in accordance with Rokan Hulu regulation No. 2 of 2015 article 12. The Community Development Program has not been fully implemented as contained in the Rokan Hulu Regulation No. 2 of 2015 article 13. The types of assistance provided are not in accordance with the CSR working areas which include education, health, infrastructure, sports, arts, and Buddhist, social and religious, environmental conservation, community economic enterprise, indigenous peoples empowerment, other work areas that significantly impact Quality of society.The concept of theory used is to use Mahmudi's theory of effectiveness, output, and outcome. The type of research used is descriptive qualitative. Data collection was done by interview Krani PT. Perkebunan Nusantara V of Sei Intan Garden of Rokan Hulu Regency, Pagaran Tapah Darussalam Subdistrict Head, Kunto Darussalam Subdistrict Head, Kembang Damai Village, Prambanan Village Chief, Darusalam and Kunto Darusalam Land Raising Societies. Interview results were analyzed by qualitative analysis approach.The results showed Output PT. Perkebunan Nusantara V of Sei Intan Garden of Rokan Hulu Regency is the existence of education and scholarship assistance, poverty alleviation and regional economic development, and public facility maintenance. In the implementation of CSR activities has not had a significant impact for the government and the community. The assistance provided is limited to performing obligations and not as a social consciousness. Outcome of CSR activities PT.Perkebunan Nusantara V area of intersection of the garden there are three that is for company, government, and society. Outcome for the company is the image of the company has increased, cooperation with stakeholders to be better, and the community becomes more innovative. For government the government is more helpful. For the community, there are scholarships for poor children, the welfare of the surrounding community is increasing, and public facilities are maintained.Keywords: Effectiveness and CSR